Assessing the influence of artificial intelligence (AI) on library services and users’ experience in the university library - Fabunmi, Samuel Olabode; Akinyemi, Omolabake Eunice (Communicate: Journal of Library and Information Science, 2025)
Artificial intelligence (AI) is one of the most recent digital innovations in this information age, and its advent has transformed how libraries perform their operations worldwide. However, despite the growing adoption of Artificial intelligence to transform library operations, assessing its effect on library services and user experience in the university library is infrequent. This study, therefore, assesses the influence of artificial intelligence (AI) on library services and users’ experiences in the university library. The study aims to know the extent of the influence of AI on library services in the university library and to investigate how AI affects users’ experience in the university library. The study used a descriptive survey research design. Two self-structure questionnaires were used to obtain data from library staff and library users in the Federal University of Technology, Akure, Ondo States, Nigeria. The findings reveal that the extent of the influence of AI on library services is very high. The findings also reveal that the effects of AI on users’ experience are high. Based on the findings, the study concludes that AI influences library services and users’ experience in the university library. Therefore, the study recommends that all university libraries should be encouraged to integrate AI in their respective library to enhance effective library services and improve users’ experiences.